A 3D geometric morphometric dataset quantifying skeletal variation in birds - Bjarnason, A; Benson, RBJ (Department of Paleontology of the Institut des Sciences de l’Évolution, 2021)
Macroevolution is integral to understanding the patterns of the diversification of life. As the life sciences increasingly use big data approaches, large multivariate datasets are required to test fundamental macroevolutionary hypotheses. In vertebrate evolution, large datasets have been created to quantify morphological variation, largely focusing on particular areas of the skeleton. We provide a landmarking protocol to quantify morphological variation in skeletal elements across the head, trunk, hindlimb and forelimb using 3-dimensional landmarks and semilandmarks, and present a large pan-skeletal database of bird morphology for 149 taxa across avian phylogeny using CT scan data. This large collection of 3D models and geometric morphometric data is open access and can be used in the future for new research, teaching and outreach.